Social losses predict a faster onset and greater severity of obsessive-compulsive disorder - Destrée, Louise; Albertella, Lucy; Torres, Albina R. [UNESP]; Ferrão, Ygor A.; Shavitt, Roseli G.; Miguel, Euripedes C.; Fontenelle, Leonardo F. [UNESP] (Elsevier, 2020)
Background: While stressful life events increase the risk of developing a range of psychiatric disorders, including obsessive-compulsive disorder (OCD), their ability to precipitate specific obsessive-compulsive symptoms' dimensions is unknown. Here we aimed to evaluate the potential role of three different types of stressful life events, herein termed losses (death of a loved one, termination of a romantic relationship and severe illness) in predicting the speed of progression from subclinical to clinical OCD and the severity of specific OCD dimensions in a large multicentre OCD sample. Methods: Nine hundred and fifty-four OCD outpatients from the Brazilian OCD Research Consortium were included in this study. Several semi-structured and structured instruments were used, including the Structured Clinical Interview for DSM-IV Axis I Disorders, the Yale-Brown Obsessive-Compulsive Scale, the Dimensional Yale-Brown Obsessive-Compulsive Scale, the Brown Assessment of Beliefs Scale, the Beck Depression Inventory, the Beck Anxiety Inventory and the Yale OCD Natural History Questionnaire. Regression models investigated the interaction between types of loss and gender to predict speed of progression from subclinical obsessive-compulsive symptoms to OCD, and the severity of five symptom dimensions. Results: While termination of a relationship was associated with a faster speed of progression from subthreshold to clinical OCD, the death of a loved one was associated with increased severity of hoarding symptoms. There was also an interaction between gender and experiences of death, which predicted a faster speed of progression to OCD in males. Conclusions: Stressful life events have the ability to accelerate the progression from subclinical to clinical OCD, as well as impact the severity of specific OCD dimensions. Gender also plays a role in both the progression and severity of symptoms. These findings suggest that stressful life events may represent a marker to identify individuals at risk of progressing to clinical OCD.
Keywords: Etiology; Gender; OCD; Onset; Stressful life events; Subthreshold